Tingkat Partisipasi Angkatan Kerja (TPAK) Perempuan Antar Kabupaten Di Propinsi Riau - Muhammad Hidayat; Muhammad Fikry Hadi; Sutrisno Sutrisno (MediaTrend, 2017)
This study aims to analyze the trend of labor force participation rate of women district in Riau Province, identify and analyze the factors that affect labor force participation rate of female among the districts in the province of Riau. The analytical tool used in the form of panel data regression analysis to determine the influence of independent variables on the dependent variable that includes the number of people who take care of the household, the number of school-age population and education of the labor force participation rate of female. Based on the results of data processing can be concluded: Districts with the highest labor force participation rate is the District Rokan Hulu followed by the District of Bengkalis and Pelalawan District. While the district the lowest labor force participation rate Meranti-Islands district. The Population taking care of the household and school-age significantly influences the Labor Force Participation Rate of female, while education does not affect the Labor Force Participation Rates of female inter-districts in Riau province.